Climate Signatures on Lake And Wetland Size Distributions in Arctic Deltas - Tejedor, Alejandro (2021)
Lake areas in arctic deltas exhibit a lognormal distribution associated with a simple mechanistic growth process. 2. Wetland areas exhibit a power law distribution consistent with inundated topography. 3. Colder arctic deltas have larger average lake sizes, likely due to thicker permafrost restricting sub-lake hydrologic connectivity.